2021
DOI: 10.21037/tcr-20-2119
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for patients with metastatic breast cancer: a literature review

Abstract: Background: To treat metastatic breast cancer (MBC) more precisely, many efforts have been made to identify prognostic factors of MBC in many studies. This review aims to qualitatively summarize these studies and to provide a reference for the research of MBC.Methods: Relevant papers were searched on PubMed, with the search terms including MBC, prognostic factors and prognosis, and the studies aimed at exploring prognostic factors for patients with histologically confirmed MBC, including stage IV at initial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Mortality is high with a median survival of 3 years, but heterogeneity in the chances of survival has been recognized (3). Studies of survival predictors beyond the extent and sites of metastases in dnMBC have identified correlates with characteristics that closely parallel known prognostic factors in early non-metastatic breast cancer, such as age, race, tumor size, histological grade, and hormone receptor status (3)(4)(5)(6)(7). There is emerging information that lymph node involvement might be a major factor that affects survival in distant stage breast cancer (7).…”
mentioning
confidence: 99%
“…Mortality is high with a median survival of 3 years, but heterogeneity in the chances of survival has been recognized (3). Studies of survival predictors beyond the extent and sites of metastases in dnMBC have identified correlates with characteristics that closely parallel known prognostic factors in early non-metastatic breast cancer, such as age, race, tumor size, histological grade, and hormone receptor status (3)(4)(5)(6)(7). There is emerging information that lymph node involvement might be a major factor that affects survival in distant stage breast cancer (7).…”
mentioning
confidence: 99%